1997
DOI: 10.1104/pp.114.4.1141
|View full text |Cite
|
Sign up to set email alerts
|

Roles of Higher Plant K+ Channels

Abstract: Living organisms maintain a cellular solute composition very different from that of the externa1 environment. This implicitly requires the transport of solutes across the cell membrane, and ion channels are integral membrane proteins that play indispensable roles in such transport. In the past dozen years, radical advances have aided in our understanding of ion channel function and regulation in higher plants. Nowhere are these advances more striking than with respect to K+ channels, where the synergistic appl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
123
0
4

Year Published

1999
1999
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 196 publications
(130 citation statements)
references
References 51 publications
3
123
0
4
Order By: Relevance
“…In guard cells, as in animal cells, turgor is also regulated by the membrane channels and pumps. Studies have shown that the inward (I Kin ) and outward K + channels (I Kout ) responsible for K + fluxes across the plasma membrane are among the most important channels in turgor regulation in guard cells (Assmann 1993;Blatt & Grabov 1997;Maathuis et al 1997). Moreover, as in animal cells, osmotic stress can regulate the activity of these membrane channels and thereby control the cell volume (or turgor) (Liu & Luan 1998).…”
Section: Osmosensing Of Ion Channels: An Aba-independent Pathwaymentioning
confidence: 99%
“…In guard cells, as in animal cells, turgor is also regulated by the membrane channels and pumps. Studies have shown that the inward (I Kin ) and outward K + channels (I Kout ) responsible for K + fluxes across the plasma membrane are among the most important channels in turgor regulation in guard cells (Assmann 1993;Blatt & Grabov 1997;Maathuis et al 1997). Moreover, as in animal cells, osmotic stress can regulate the activity of these membrane channels and thereby control the cell volume (or turgor) (Liu & Luan 1998).…”
Section: Osmosensing Of Ion Channels: An Aba-independent Pathwaymentioning
confidence: 99%
“…10B). It is noteworthy that the time-dependent K 1 inwardly rectifying channels, often reported in root cells (Maathuis et al, 1997), were not observed in any protoplast tested (n 5 7; Fig. 10A).…”
Section: Pharmacology and Selectivity Of Oracmentioning
confidence: 99%
“…To date, most of the information on the biophysical characteristics and physiological roles of ORCs has been obtained by means of electrophysiological studies conducted on highly simplified systems such as protoplasts, membrane fragments or heterologous expression systems (Maathuis et al , 1997;Ward, 1997;Miller & Zhou, 2000). It is clear that the results obtained by these attractive approaches could acquire more physiological significance if combined with, or compared with, results obtained with techniques that induce as little physiological perturbation as possible (Tester, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…The involvement of potassium in fundamental processes of plant biology is strictly related to the evolution of different K + transport systems in the cell plasma membrane (Maathuis et al , 1997;Chrispeels et al , 1999). Several studies have revealed that the movement of K + across the plasma membrane involves a multitude of transport proteins, including carriers and channels (Chrispeels et al , 1999).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation